Water security assessment of groundwater quality in an anthropized rural area from the atlantic forest biome in Brazil - Vieira, Igor Fellipe Batista; Neto, Fernando Cartaxo Rolim; Carvalho, Marilda Nascimento; Caldas, Anildo Monteiro; Costa, Renata Cristina Araújo [UNESP]; da Silva, Karolyne Santos; Parahyba, Roberto da Boa Viagem; Pacheco, Fernando Antonio Leal; Fernandes, Luís Filipe Sanches; Pissarra, Teresa Cristina Tarlé [UNESP] (MDPI, 2020)
The exploitation of natural resources has grown mainly due to the high rate of population growth that changed over time around the planet. Water is one of the most needed resources essential for survival. Despite all the efforts made to improve water security, an environmental impact related to anthropogenic influence remains of great concern, which is the alteration of surface and groundwater quality. In many regions around the world, there is limited or no access to rural and urban water supply while there is a need to improve sanitation facilities. This work evaluated the spatial distribution of groundwater and surface water quality as well as their changes in wet and dry seasons of the tropical climate in the Atlantic Forest Biome. The study area is under anthropogenic influence, which is in the municipality of Igarassu, Pernambuco State, Brazil. The analysis of the raw water was based on Standard Methods for Examination of Water and Wastewater, as referenced in the Brazilian Ministry of Health Consolidation Ordinance that sets standards for drinking water. The temporal analyses indicated a variation on water quality from the wet to the dry seasons, whereas the spatial results revealed deviations from the Brazilian's Water Supply Standards for some physicochemical parameters. There was an increase in the values of some parameters during the wet season in some hydrological compartments. The anthropized rural area from the Atlantic Forest Biome is affecting the water quality. It is, therefore, necessary to develop environmental policies and put them into practice by implementing engineering projects that guarantee proper treatment for raw water in order to bring the water quality back to a good status in this region.
Keywords: Drinking water; Environmental monitoring; Groundwater; Surface water; Water quality